Depression of pyrite in a low-alkaline medium with added calcium hypochlorite: Experiment, visual MINTEQ models, XPS, and ToF–SIMS studies. (September 2019) - Bai, Shaojun; Yu, Pan; Li, Chunlong; Wen, Shuming; Ding, Zhan
Graphical abstract: Highlights: The addition of Ca(ClO)2 at pH 8.7 enhances pyrite hydrophilicity and decreases flotation recovery by ∼60% with KBX. Hydrophilic species exist in the form of iron carbonyl, hematite, hydroxy calcium, and calcium deposits. The thickness of the formed hydrophilic species and dixanthogen on samples was determined by ToF–SIMS analysis. Semiquantitative determination of specific hydrophilic species on samples was conducted by ToF–SIMS analysis. Abstract: Ca(ClO)2 is a promising depressant for differential flotation of base metal sulfide ores. However, limited studies have been conducted on the depression mechanism of Ca(ClO)2 for pyrite. This study investigates the effect of Ca(ClO)2 on pyrite flotation with butyl xanthate (KBX) in a low-alkaline medium. The addition of Ca(ClO)2 at pH 8.7 enhances pyrite hydrophilicity and decreases flotation recovery by ∼60%. Solubility tests and Visual MINTEQ model analysis indicate that Ca(ClO)2 promotes the dissolution of pyrite and produces more hydrophilic species on the pyrite surface. Contact angle measurement results confirm that adding Ca(ClO)2 increases the number of hydrophilic species. XPS study indicates that the depressing effect of Ca(ClO)2 on pyrite is due to the formation of CaSO4 and Fe(OH)3 and the adsorption of Ca(OH) + on the surface. ToF–SIMS results provide strong evidence that adding Ca(ClO)2 increases the amount of hydrophilic species and decreases dixanthogen adsorption onto the pyrite surface. The thickness of the whole formed hydrophilic species is approximately 41.7 nm, and the thickness of the formed dixanthogen is few nanometers. Based on semiquantitative determination, the number of hydrophilic species follows the order of hydroxy calcium > iron carbonyl > hematite > calcium sulfate > calcium carbonate. Overall, hydrophilic species reduce adsorption of dixanthogen and significantly reduce the flotation performance of pyrite.